Role of Histone Deacetylases in Skeletal Muscle Physiology and Systemic Energy Homeostasis: Implications for Metabolic Diseases and Therapy - Tian, Haili; Liu, Sujuan; Ren, Jun; Lee, Jason Kai Wei; Wang, Ru; Chen, Peijie (Frontiers in Physiology, 2020)
Skeletal muscle is the largest metabolic organ in the human body and is able to rapidly adapt to drastic changes during exercise. Histone acetyltransferases (HATs) and histone deacetylases (HDACs), as the two major enzyme families, control the biological process of histone acetylation and deacetylation. Balance between these two enzymes serves as an essential element for gene expression, metabolic and physiological function. Genetic KO/TG murine models reveal that HDACs possess pivotal roles in maintaining skeletal muscles metabolic homeostasis, regulating skeletal muscles motor adaptation and exercise capacity. HDACs may be involved in mitochondrial remodeling, insulin sensitivity regulation, and turn on/off of metabolic fuel switching, orchestrating physiological homeostasis of skeletal muscles from the process of myogenesis. Moreover, many myogenic factors and metabolic factors are modulated by HDACs. HDACs are considered as therapeutic targets in clinical research for treatment of cancer, inflammation, neurological and metabolic-related diseases. Here this review will focus on physiological function of HDACs in skeletal muscles and aiming to provide new ideas for the treatment of metabolic diseases.